Pelatihan Manajemen Organisasi untuk Meningkatkan Peran Pemuda dalam Berwirausaha - Viona Ananda Putri; Wahyu Eko Pujianto (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the existence of organizational management training to increase the role of youth in carrying out entrepreneurial activities among youth in the Sidoarjo Regency area. A qualitative approach is used as a research method. It uses a type of qualitative descriptive research that involves information in the form of written and spoken words based on objects that have been observed. The research results show that organizations in youth businesses in the Sidoarjo area apply the implications of organizational management training strategically and prioritize organizations that are efficient and dedicated to the organization's vision and mission. The strategy carried out includes an implicative approach. Before carrying out entrepreneurial activities, mentors' training and assistance is necessary for the millennial generation who want to open a business. Entrepreneurial skills are also needed to start a business by carrying out more complex applications for young entrepreneurs. Through various existing implications, theoretically, the application of organizational management training can increase competent human resources to be able to create dynamic global competition.